Optimization and kinetic study of treatment of dye contaminated wastewater using bio-composite synthesized from natural waste - Iqbal, Mana; Hanif, Muhammad Asif; Rashid, Umer; Jilani, Muhammad Idrees; Alharthi, Fahad A.; Kazerooni, Elham Ahmed (Multidisciplinary Digital Publishing Institute, 2023)
The main objective of the present research project was to investigate the possibility of using low cost, eco-friendly, and easily available adsorbents such as mint biomass and marble stone waste for the removal of dyes - DRIM blue HS-RL and DRIM black ep-B from wastewater by an efficient procedure - Adsorption. Nine different combinations of these adsorbents were prepared with and without modification using sodium metasilicate and potassium ferricyanide. Spectroscopic analysis was car-ried out to investigate λmax of the dyes. Adsorbent nanocomposites were characterized using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and zeta () potential. Adsorption equilibrium studies were investigated by determining the adsorption at following con-ditions; initial dye concentrations (5-50ppm), adsorbent doses (0.005-0.5g), contact time (15-240 minutes), temperatures (300C -700C) and pH (5-10). However, of all the nine adsorbents, MTPF showed maximum adsorption capacity at 50ppm initial dye concentration, 0.005 g dosage of adsorbent and 240 minutes’ contact time for both dyes. DRIM Blue HS-RL was adsorbed efficiently at 6 pH and temper-ature 600C and that of DRIM black ep-B at pH 5 and temperature 500C by MTPF (Mint-Tawera com-posite treated with Potassium Ferricyanide). Among various adsorption isotherms (Langmuir, Du-binin Radushkevich, Freundlich, Herkin Jura, and Temkin isotherms), some adsorbent followed Freundlich isotherm while the others followed Langmuir isotherm. The best fit model was decided based on their high R2 value and agreement between qe calculated from isotherms and that obtained experimentally. At equilibrium concentration application of kinetic models (pseudo first order, and pseudo second order), revealed that the best fit model was pseudo 2nd order kinetic model for both dyes, as their R2>0.9, and qe calculated was close to qe experimental.